2010
DOI: 10.1253/circj.cj-10-0110
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Effects of Statins - Basic Research and Clinical Perspectives -

Abstract: Statins are 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors, which are widely used to lower serum cholesterol levels in the primary and secondary prevention of cardiovascular disease. Recent experimental and clinical evidence suggest that the beneficial effects of statins may extend beyond their cholesterol lowering effects, to include so-called pleiotropic effects. These cholesterol-independent effects include improving endothelial function, attenuating vascular and myocardial remodeling,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
188
0
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 489 publications
(209 citation statements)
references
References 131 publications
4
188
0
9
Order By: Relevance
“…Such antioxidative effects of probucol might be more important than its free radical scavenging activity in terms of the prevention of atherosclerosis. Although statins are also reported to have such anti-oxidative effects (i.e., an increase in heme oxygenase-1 expression and a decrease in NAD(P)H oxidase activity [19]), probucol but not atorvastatin decreased the plasma and plaque OxLDL levels, indicating the antioxidative effect of probucol differs in vivo from that of atorvastatin. Previous work found that plasma OxLDL levels in apolipoprotein E-knockout mice measured by our sandwich ELISA procedure preceded the formation of extensive atherosclerotic lesions, suggesting that OxLDL has pro-atherosclerotic properties in vivo [22].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Such antioxidative effects of probucol might be more important than its free radical scavenging activity in terms of the prevention of atherosclerosis. Although statins are also reported to have such anti-oxidative effects (i.e., an increase in heme oxygenase-1 expression and a decrease in NAD(P)H oxidase activity [19]), probucol but not atorvastatin decreased the plasma and plaque OxLDL levels, indicating the antioxidative effect of probucol differs in vivo from that of atorvastatin. Previous work found that plasma OxLDL levels in apolipoprotein E-knockout mice measured by our sandwich ELISA procedure preceded the formation of extensive atherosclerotic lesions, suggesting that OxLDL has pro-atherosclerotic properties in vivo [22].…”
Section: Discussionmentioning
confidence: 96%
“…These drugs also have various antiinflammatory activities [13], [19]. Plasma CRP concentration is a clinically important marker of increased risk of cardiovascular disease, and CRP concentration in rabbits is increased by feeding a cholesterol-enriched diet for longer than 12 weeks [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pleiotropic effects of statin therapy include increased nitric oxide bioavailability, antithrombotic, and anti-inflammatory effects (9,10). However, the benefits of vascular protection may vary according to the potency of statin or pharmacokinetic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…A third mechanism reported hypothesizes that statins regulate the activity of eNOS via their effects on caveolin-1. Caveolin-1 is an integral membrane protein that binds to eNOS in caveolae, thereby directly inhibiting the production of NO (38). The function of allopurinol, a xanthine oxidase inhibitor, in the prevention and treatment of hyperuricemia was limited due to the inhibitory effect of allopurinol on the biosynthesis of UA, evident only when high levels of UA accumulated in the blood circulation (39).…”
Section: Discussionmentioning
confidence: 99%